Deteksi Dini Pemakaian MKJP (Metode Kontrasepsi Jangka Panjang) Pada Wanita Usia Subur Di Desa Candirejo Mijen Kab.Semarang - Setiawati, Erna; Sundari, Sundari; Nasifah, Isri (Jurnal Pengabdian Dharma Bakti, 2019)
Based on national data of BKKBN (National Family Planning Coordinating Board) of Central Java Province and MKJP usage data in ungaran subdistrict obtained data that KB MKJP acceptor is still lower than KB non MKJP acceptor.The purpose of this dedication is to improve the characteristics of women so that it can reduce the high risk group of MKJP usage where it is in line with the government program that is the recommendation of using MKJP or increase the satisfaction on the WUS who already use MKJP contraception. Devotion is done through counseling and examination of maternal health conditions that include examination of body weight, blood pressure, cholesterol. This devotion is done to 26 women of childbearing age in the village area candirejo kab. Semarang and implemented on 13 October and 5 November 2017.Evaluation conducted by giving questions on the pre and post counseling, while the examination data is written on the recap examination.The result of this devotion is from 11 IUD acceptors there are 17% have mild anemia while from 15 Acceptor Implant as much as 13% have anemia, equal to 36% IUD acceptor and 27% acceptor Implant has increased blood sugar level when, the increase of cholesterol level on Iud acceptor equal to 27% and 33% on the Implant acceptor. It is hoped that this dedication will contribute significantly to the increase of KB MKJP participants.Keyword : Early Detection, MKJP, WUS